STRATEGI KESOPANAN TINDAK TUTUR PERMINTAAN DALAM BAHASA ANAK PADA KOMIK CHIBI MARUKO CHAN (VOLUME 1-16) - Sandy, Meli; Rahayu, Nana; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research’s goal is to know politeness strategies used by childs when speech a demand and what factors affect politeness when speech. This research object are childs with age range between 5-12 years old from Chibi Maruko Chan manga with demand speech (either demand for goods or service) taken as data. This research used descriptive and qualitative approach to analyze object based on theories used. The research datas taken by read Chibi Maruko Chan manga then group the demand speech by type it. Author use politeness strategies theory by Brown and Levinson. This research result show that childs on Chibi Maruko Chan manga used three kinds politeness strategies when speech a demand, its possitive politeness, negative politeness, and off record. This research could be the basis for further studies involving more subjects to ensure the generalizability of the results.Keywords: politeness strategy, speech act, demand speech